Comprehensive Compulsory Health Insurance As A Strategic Option In Future Health Development Process (analytical study in Latakia governorate) - Mohammad, Osama; Asaad, Bassel (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The Comprehensive Health Insurance System is one of the most important systems recommended by WHO. This system is of great importance in providing health care services to all citizens as fair as possible. The comprehensive health insurance system is an appropriate option for the current situation in Syria. The aim of the study is to examine the reality of the public health insurance system and its disadvantages, and propose a comprehensive health insurance model that can be applied in the Syrian Arab Republic that takes into consideration the current situation. The method adopted in the study is the analytical descriptive approach. A questionnaire was designed and distributed to 450 workers in the public sector in order to measure their satisfaction with the current health insurance system. The importance of the research is one of the studies that focuses on the possibility of applying a proposed model that can help in providing the necessary health services to all citizens in a fair manner in light of the current crisis of decreasing income level and increasing demand for government health services. The results of the study are as follows: The ineffectiveness and fairness of the current government health insurance system, the acceptance and satisfaction of the public about the comprehensive health insurance and its installments, The importance of the proposed insurance system in securing adequate funding for the health services sector. The proposed model could form the basis for a future health development strategy.